Social determinants of health are associated with low uptake of daily HIV pre-exposure prophylaxis and future uptake of long-acting formats: a survey of Black and Latina/x/e transfeminine adults in Chicago - Thompson, Hale M.; Schafer, Tommy; Ortiz, Reyna; Leslie, J. Silas; Rivera, Juan (Frontiers in Public Health, 2025)
IntroductionThe transgender population in the United States continues to experience disproportionately high HIV prevalence, and Black and Latina transgender women, in particular, account for more than half of the population’s new diagnoses. Uptake of pre-exposure prophylaxis (PrEP), the daily oral HIV prevention pill, among Black and Latina transfeminine adults has lagged. This community-engaged, HIV status-neutral study served as an initial investigation of Black and Latina/x/e transfeminine adults’ attitudes toward various long-acting formats of PrEP relative to the daily pill.MethodsAn online survey was conducted in Chicago, IL, in 2023 (N = 198). A multiple logistic regression analysis was conducted to identify factors associationed with the most highly preferred long-acting PrEP format. Second, we compared individuals who would be indicated for daily PrEP based on the 2021 CDC eligibility guidance with those reporting current uptake of the daily pill.ResultsOur findings indicate having a college degree or higher (adjusted odds ratio (aOR) = 6.73 [95% CI: 2.18–20.81], p < 0.001) and full-time employment (aOR = 2.70 [95% CI: 1.19–6.17], p = 0.018) were associated with reporting a preference for taking the monthly pill while controlling for age group, race, and sexual orientation. Second, those currently taking PrEP were disproportionately stably housed, and 54% reported no CDC-endorsed indications. The positive predictive value of the 2021 CDC PrEP eligibility guidance was 0.30.DiscussionSimilar to other populations vulnerable to HIV, social determinants of health were associated with a preference for the long-acting pill and with current uptake of the daily pill. These findings signal a need for additional research into innovative PrEP implementation strategies that mitigate the structural barriers that transfeminine adults face.